2013
DOI: 10.5336/medsci.2012-31779
|View full text |Cite
|
Sign up to set email alerts
|

Experience of 352 Carotid Endarterectomy Cases Operated on without Any Shunt and a Technical Modification: Thirty-Day Results

Abstract: A AB BS ST TR RA AC CT T O Ob bj je ec ct ti iv ve e: : The necessity for an indwelling arterial shunt during carotid endarterectomy (CEA) is one of the most widely debated and long-standing controversies in carotid surgery. We developed a modified technique for carotid endarterectomy without using a shunt and have achieved successful results with this procedure. The aim of this study is to present these 352 isolated CEA cases and evaluate the results. M Ma at te er ri ia al l a an nd d M Me et th ho od ds s: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It has been reported that eversion CEA has a lower restenosis rate than conventional CEA closure techniques and thus superior long-term durability. Today, eversion CEA is one of the most preferred technique with a postoperative stroke rate between 0.6 and 2.5 % [ 20 22 ]. In this study all of the cases were operated with eversion CEA technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that eversion CEA has a lower restenosis rate than conventional CEA closure techniques and thus superior long-term durability. Today, eversion CEA is one of the most preferred technique with a postoperative stroke rate between 0.6 and 2.5 % [ 20 22 ]. In this study all of the cases were operated with eversion CEA technique.…”
Section: Discussionmentioning
confidence: 99%
“…In our clinique postoperative symptomatic stroke rate is under 2 % after CEA [ 22 ]. In this study, we found 8 new ischemic images on DWI which 1 of them symptomatic (1.9 %), 7 of them asymptomatic –silence- ischemia (13.7 %) after CEA.…”
Section: Discussionmentioning
confidence: 99%